Social dimension of innovation - Bukowski, Andrzej; Rudnicki, Seweryn; Strycharz, Jan (Journal of Public Governance, 2018)
This article deals with the issue of what we call social aspects of innovation. We depart from asserting that dominating stance in designing public policy aimed at innovation promotion in Poland omits its social aspects. This – we state – is a threat to its effectiveness and efficiency. In the article we bring forward and explain four maladies of innovation public policy as we see them. Firstly we talk about the technological bias – most of the policies are aimed in promoting high-tech and are channeled through engineers omitting social aspects and social expertise. Secondly, we explain the focus innovation policies have on promoting highly formalized and institutionalized sources of knowledge not taking elements like tacit knowledge and social skills into consideration. Thirdly, we explain the preference the policies have on promoting top-down or push type innovation at the cost of forming the adequate demand which would then later drive the supply of innovation. Lastly we touch upon the utter dismissal of social sciences as being an important source of knowledge on innovation diffusion; but also the source of innovation itself.